Is increased cross-border mobility incompatible with redistributive welfare states? The North European case - Bjørn Hvinden (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2006)
The paper examines the claim that international migration and increased ethnic diversity challenge the sustainability and legitimacy of redistributive welfare states. Immigration might potentially lessen pressures related to demographic ageing, labour shortages in welfare services and the funding of future pensions in many European countries. The paper discusses three accounts of why a mutually beneficial relationship between immigration and welfare state sustainability so far has not been achieved. The first account claims that redistributive welfare states are undermined because increased immigration-based ethnic diversity diminishes social solidarity. The second account argues that immigration, especially from non-western countries, threatens the sustainability of redistributive welfare provision because there is an unfortunate interplay between the level of qualifications of immigrants and the work disincentives created by fairly generous and accessible social security benefits. The third account attributes the problems of immigrants' economic integration to discriminatory attitudes and practices of key decisionsmakers in the receiving countries, especially from employers and staff in employment and educational services. The paper questions the first of these accounts on theoretical and empirical grounds. The last part of the paper argues that there is a need for better longitudinal data about the employment contexts and work conditions of immigrants in receiving countries and the prevalence of discrimination, in order to enable an assessment of the relative merits of the second and third account.
Keywords: 320